Assessment of cystatin C and CCL14 as predictive and diagnostic biomarkers for contrast-induced nephropathy - Mahmood, K. A.; Ewadh, M. J.; Al-Saad, S. F. (Regulatory Mechanisms in Biosystems, 2024)
Contrast-induced nephropathy (CIN) is kidney dysfunction caused by radiocontrast agents, occurring 48–72 hours after their administration. The early prediction of CIN would be valuable in order to limit the damage caused by this condition. The present study aimed to evaluate the serum levels of chemokine (C-C) motif ligand-14 (CCL14), insulin-like growth factor-binding protein-7 (IGFBP7), cystatin C, and creatinine as novel biomarkers that predict contrast-induced nephropathy. This study aimed to assess the predictive value of cystatin C and CCL14 biomarkers for CIN development. The ELISA test was used to quantify serum levels of CCL14, IGFBP7, and cystatin C 2 days after exposure to contrast media in 44 patients with normal renal function before being scheduled to undergo coronary angiography (control group) and 2 days after exposure to contrast media in the contrast-induced nephropathy (CIN) group, and all data were compared. Levels of serum creatinine in CIN and control groups were also compared. The levels of the three biomarkers at 2 days after exposure to contrast media in the CIN group were significantly higher than those in the control group, while the level of serum creatinine was significantly higher than that in the control group. Moreover, the levels of CCL14, IGFBP7, and cystatin C were positively correlated with serum creatinine at 2 days after exposure to contrast media in the CIN group. This study demonstrated that the serum levels of CCL14, IGFBP7, and cystatin C could be potential predictors for CIN.